Analysis of Coal, Flyash and Soil For Agricultural Use - Chandra Deshmukh, Naresh; Kumar Sarway, Prakash; Prasad Tyagi, Naresh; Bawaria, Amit; Shrivastava, Seema (Asian Journal of Chemistry, 2016)
In the present work, various physicochemical properties of flyash, obtained from National Thermal Power Corporation of Korba district have been reported.